Heteroleptic transition metal complexes of Schiff‐base‐derived ligands exert their antifungal activity by disrupting membrane integrity. (21st August 2019) - Dar, Ovas Ahmad; Lone, Shabir Ahmad; Malik, Manzoor Ahmad; Wani, Mohmmad Younus; Talukdar, Md Ikbal Ahmed; Al‐Bogami, Abdullah Saad; Hashmi, Athar Adil; Ahmad, Aijaz
Abstract : Development of new treatment strategies and chemotherapeutic agents is urgently needed to combat the growing multidrug resistant species of Candida . In this direction, a new series of Cu (II), Co (II), Ni (II) and Zn (II) heteroleptic complexes were synthesized, characterized and evaluated for antifungal activity. Based on spectral characterization and physical measurements, an octahedral geometry was assigned to [Co(L1)(L2)ClH2 O] (C2 ), [Ni(L1)(L2)ClH2 O] (C3 ), [Zn(L1)(L2)ClH2 O] (C4 ) complexes, while a distorted octahedral geometry was assigned to [Cu(L1)(L2)ClH2 O] (C1 ) complex. All the synthesized compounds were tested for antifungal activity against 11 Candida albicans isolates, including fluconazole (FLC)‐resistant isolates, by determining minimum inhibitory concentrations (MIC) and minimum fungicidal concentrations (MFC), following CLSI guidelines. The mechanism of their antifungal activity was assessed by studying their effect on the plasma membrane using flow cytometry and quantifying the ergosterol contents. All the test compounds showed varying levels of antifungal activity. Both the ligands showed moderate antifungal activity with a median MIC value of 100 μg/mL with no fungicidal activity. Compound C3 was the most potent compound with median MIC and MFC values of 0.10 and 1.60 μg/mL, respectively. Flow cytometry analysis revealed that these compounds at MFC values disrupt the cell membrane, resulting in propidium iodide entering the cells. These compounds also reduced a considerable amount of ergosterol content after treating the cells with MIC and sub‐MIC values. This study indicates that these compounds have high antifungal activity against C. albicans, and have the potential to be developed as novel antifungal drugs. Abstract : A Schiff base ligand‐based heteroleptic Ni (II) complex showed potential membrane‐targeted antifungal activity.